Income security programs and retirement in Sweden - Mårten Palme; Ingemar Svensson (Stockholm School of Economics, The Economic Research Institute (EFI), 2001)
We examine the effects of economic incentives inherent in pension schemes and income security programs on retirement behavior in the Swedish labor market. We use social security wealth and three alternative measures of accrual (one-year benefit accrual, peak value and option value). The social security system, occupational pensions as well as insurance on the labor market, i.e., unemployment, sickness and disability insurance are considered. We estimate a model using panel data on about 30 000 men and women born between 1927 and 1940, observed between 1983 and 1997. The model is then used to simulate the effects of two alternative systems: one where eligibility for benefits in the prevailing system is delayed by three years and another where replacement levels are reduced.
Keywords: J20; J21; J26; 330; benefit accrual; peak value; option value; disability insurance